1999
DOI: 10.1207/s15327914nc352_18
|View full text |Cite
|
Sign up to set email alerts
|

High Intake of Specific Carotenoids and Flavonoids Does Not Reduce the Risk of Bladder Cancer

Abstract: An analysis of a previously completed Spanish multicentric case-control study of bladder cancer was carried out using new available data on the contents in foods of specific carotenoids (alpha-carotene, beta-carotene, lutein, and lycopene) and flavonoids (quercetin, kaempferol, myricetin, and luteolin) to investigate the relationship of these phytochemicals with bladder cancer. The study included 497 cases first diagnosed with bladder cancer, 547 neighborhood controls, and 566 hospitals controls, matched by ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 6 publications
1
28
2
1
Order By: Relevance
“…There are few contrary reports [28][29][30] that may be due to differences in bioavailability of the various flavonoids, and their effects on individual cancer sites cannot be excluded meriting further investigation.…”
Section: E V I D E N C E O F a N T I C A N C E R E F F E C T S A Ementioning
confidence: 94%
“…There are few contrary reports [28][29][30] that may be due to differences in bioavailability of the various flavonoids, and their effects on individual cancer sites cannot be excluded meriting further investigation.…”
Section: E V I D E N C E O F a N T I C A N C E R E F F E C T S A Ementioning
confidence: 94%
“…To our knowledge, only three studies (Garcia et al, 1999;Michaud et al, 1999;Zeegers et al, 2001a) have published findings for the relation between individual carotenoid intakes and bladder cancer risk. No associations were observed for alphacarotene, beta-carotene, lycopene or lutein intakes in these publications, but an inverse association was reported for betacryptoxanthin in the Netherlands Cohort Study, which was particularly strong among heavy smokers (Zeegers et al, 2001a).…”
Section: Epidemiologymentioning
confidence: 99%
“…Clinical trials attempt to correlate polyphenolic intake with prevention of a particular cancer, showing a decreased risk for different types of cancer [7 -10] or a diminished recurrence of cancer [11,12] after the consumption of flavonoids or certain foods or drinks (tea) rich in these phenolic compounds. In contrast, certain human studies have also shown no beneficial effects [13,14] or have failed to find a positive association between intake of flavonoids and reduced risk for different types of cancer [15,16]. However, it should be highlighted that assessing the real impact of such constituents on human health is difficult, when consider that in many cases the exact composition of foods and the bioavailability of active molecules are not known.…”
Section: Introductionmentioning
confidence: 99%